Matematică
cococostache
6

[latex] \frac{x-1}{3} [/latex] -3(2x -[latex] \frac{5-2(x-1)}{4} [/latex]) ≥ x+2[latex] \frac{3}{4} [/latex]

+0
(1) Răspunsuri
Cont şters

aducem paranteza la acelasi numitor (x-1)/3-3[(8x/4-(5-2x+2)/4]≥x+11/4 (x-1)/3-3[(8x-7+2x)/4]≥x+11/4 (x-1)/3-3(10x-7)/4≥x+11/4 (x-1)/3-(30x-21)4≥x+11/4 aducem la acelasi numitor (4x-4-90x+63)/12≥(4x+11)/4 (-86x+59)12≥(4x+11)/4 -86x/12-4x/4≥11/4-59/12 aducem la acelasi numitor (-86x-12x)/12≥(33-59)/12 -98x/12≥-26/12 inmultim  cu -12 x≤26/98 x/43/49

Adaugă răspuns